Simultaneous Determination of Diamide Insecticides in Honeysuckle Using a Modified QuEChERS Based on Carboxylated Multi‐walled Carbon Nanotubes and UPLC‐PDA. Issue 25 (1st July 2022) - Li, Guangling; Yang, Jinghua; Zhang, Youduo; Li, Songwei; Liu, Runqiang
Abstract: Pesticide residue has become a bottleneck for developing the Chinese herbal medicine industry. Diamide insecticides have been approved to control various crop pests in many countries around the world. In this study, a multi‐residue method was established and validated for six diamides (flubendiamide, cyantraniliprole, cyclaniliprole, chlorantraniliprole, tetrachlorantraniliprole, and broflanilide) in honeysuckle matrix. In this methodology, the combined purifier based on the carboxylated multi‐walled carbon nanotubes (MWCNT‐COOH) exhibited good purification efficiency and effectiveness to the acetonitrile extract of honeysuckle. The instrumental analysis was completed perfectly in 16 minute on an ultra performance liquid chromatography‐photodiode array detector (UPLC‐PDA). The recoveries of six diamides ranged from 79 % to 107 %, with the relative standard deviations (RSD) less than 12.5 %. Limits of quantitation (LOQ) of six analytes ranged from 0.009 to 0.014 mg kg −1 in the honeysuckle sample. The results imply the method is reliable for detecting the six diamides in honeysuckle. Abstract : Honeysuckle, a multipurpose herb in self‐medication either with or without pharmaceutical preparation, was a gift of nature. However, one genuine concern is that the quality of this herb is being inescapably overshadowed by pesticide residues. This study proposed a very promising multiresidue method for six diamide pesticides in honeysuckle using a modified QuEChERS (Quick, Easy, Cheap, Effective, Rugged, Safe) method and UPLC‐PDA (ultra performance liquid chromatography‐photodiode array detector).